Community collective efficacy is associated with reduced physical intimate partner violence (IPV) incidence in the rural province of Mpumalanga, South Africa: findings from HPTN 068. Issue 2 (19th November 2018) - Leddy, Anna M; Lippman, Sheri A; Neilands, Torsten B; Twine, Rhian; Ahern, Jennifer; Gómez-Olivé, Francesc Xavier; DeLong, Stephanie M; MacPhail, Catherine; Kahn, Kathleen; Pettifor, Audrey E
Abstract : Background: Intimate partner violence (IPV) is a human rights violation and is associated with a variety of adverse physical and mental health outcomes. Collective efficacy, defined as mutual trust among community members and willingness to intervene on the behalf of the common good, has been associated with reduced neighbourhood violence. Limited research has explored whether community collective efficacy is associated with reduced incidence of IPV. This is of particular interest among adolescent girls and young women (AGYW) in sub-Saharan Africa, where the burden of HIV is greatest and IPV is common. Methods: We collected longitudinal data among 2533 AGYW (ages 13–20) enrolled in the HPTN 068 cohort in Mpumalanga province, South Africa between 2011 and 2016. We included participants from 26 villages where community surveys were collected during the HPTN 068 study. Collective efficacy was measured at the village level via two population-based cross-sectional surveys in 2012 and 2014. Multivariable Poisson generalised estimating equation regression models estimated the relative risk ratio (RR) between village collective efficacy scores and subsequent physical IPV 12 month incidence, adjusting for village-level clustering and covariates. Results: Thirty-eight per cent of the cohort (n=950) reported at least one episode of recent physical IPV during follow-up. For every SD higher level of collective efficacy, there was a 6% lower level of physical IPV incidence (adjusted RR: 0.94; 95% CI 0.89 to 0.98) among AGYW after adjusting for covariates. Conclusions: Community-level interventions that foster the development of collective efficacy may reduce IPV among AGYW.